The Mediterranean Protection Between Environment and Politics: Fifty Years After UNEP/MAP 1975 - Borzoni, Gianluca (HAPSc Policy Briefs Series, 2024)
The year 2025 marks the 50th anniversary of the Mediterranean Action Plan (MAP), launched under the auspices of the United Nations Environment Program (UNEP). This milestone holds profound significance, not only for the preservation of the basin, but also within the broader framework of environmental and political diplomacy over the past decades. This contribution aims to reflect on the importance of this anniversary, both as the culmination of past political initiatives and as a testament to the environmental progress achieved thus far, while drawing out key lessons that can inform future efforts.